Weather and climate services in Ethiopia: progress, challenges, and opportunities - Tola, Fetene Teshome; Dadi, Diriba Korecha; Kenea, Tadesse Tujuba; Dinku, Tufa (Frontiers in Climate, 2025)
National Meteorological and Hydrological Services (NMHS) provide weather and climate information, which supports various socio-economic sectors. The Ethiopian Meteorological Institute (EMI) has been providing essential meteorological data, forecasts, and services in support of the climate-sensitive sectors such as agriculture, water resource management, disaster risk reduction, public health, and energy among others. EMI has a long history in weather and climate services, with the first meteorological station established in 1890. The institute has made steady progress over the last seven decades. It has expanded its meteorological observation network, improved its weather and climate forecast at different time scales, has made strides in enhancing the generation and dissemination of climate information products, strengthened engagement with users, and made concerted efforts to develop its infrastructure and skilled manpower. Despite the strides it has made, EMI has faced notable challenges, which is shared with many African NMHSs, such as financial constraints, technical limitations, inadequate infrastructure, and shortages of skilled personnel. Despite the challenges, EMI has made some progress in enhancing its services, which is possible mainly because of continued government support. Even though Ethiopia is among economically weak countries, the government has continued providing sustained support to EMI. This paper examines the evolution, progress, challenges, and opportunities associated with weather and climate service in Ethiopia. By sharing lessons learned from Ethiopia’s experiences, this study provides insights into the broader role of NMHS in Africa and their contribution to sustainable development and disaster risk management.